Analysis of College Students’ Difficulties in Developing paragraph in Japanese writing - Nurjanah, Nurjanah; Supriatnaningsih, Rina; Setiawati, Ai Sumirah (Chi'e: Journal of Japanese Learning and Teaching, 2018)
This is a quantitative descriptive research that aimes to describe students’ diffulties in develophing the paragraph in Japanese writing, the causal factors, and solutions from difficulties in developing the paragraph experienced by students of Japanese Education program in Semarang  State University. Samples of this research were a total of 30 students of Japanese Education Program class 2014. The technique of collecting data  used was questionnaire. The data results obtained then were analyzed using descriptive percentage approach. The result of this research showed that  difficulties developing paragraph on Japanese essay, included determining ideas, writing topic sentences, composing supporting ideas, writing and composing with logical plot, using phrases, vocabulary and sentence patterns. Factors that affected were the lack of students' interest in reading and writing, and the students' lack of knowledge about paragraphs. The solutions that could be used to overcome these difficulties were often practicing Japanese writing, read other book references and apply vocabulary and sentence pattern to the fullest.   Penelitian ini merupakan jenis penelitian deskriptif kuantitatif yang bertujuan utuk  mendeskripsikan keulitan, faktor penyebab, dan solusi dari kesulitan mengembangkan paragraf pada karangan bahasa Jepang yang dialami oleh mahasiswa Prodi Pendidikan Bahasa Jepang Unnes. Sampel penelitian ini adalah 30 mahasiswa prodi pendidikan Bahasa Jepang angkatan 2014. Teknik pengumpulan data yang digunakan adalah menggunakan angket. Hasil data yang diperoleh dianalisis dengan pendekatan deskriptif prosentase. Hasil penelitian menunjukan bahwa kesulitan mengembangkan paragraf pada karangan bahasa Jepang meliputi menentukan ide, menulis kalimat utama, menulis dan menyusun kalimat penjelas dengan alur yang logis, penggunaan ungkapan, kosakata dan pola kalimat. Faktor yang mempengaruhinya adalah kurangnya minat mahasiswa terhadap membaca dan menulis, dan  ketidaktahuan mahasiswa tentang paragraf. Solusi yang dapat digunakan untuk mengatasi kesulitan tersebut yaitu sebaiknya sering berlatih mengarang, membaca referensi buku lain, dan menerapkan kosakata maupun pola kalimat yang sudah dipelajari secara maksimal.